Definition of important early morbidities related to paediatric cardiac surgery. (29th September 2016) - Brown, Katherine L.; Pagel, Christina; Brimmell, Rhian; Bull, Kate; Davis, Peter; Franklin, Rodney C.; Hoskote, Aparna; Khan, Natasha; Rodrigues, Warren; Thorne, Sara; Smith, Liz; Chigaru, Linda; et al.
Abstract: Background: Morbidity is defined as a state of being unhealthy or of experiencing an aspect of health that is "generally bad for you", and postoperative morbidity linked to paediatric cardiac surgery encompasses a range of conditions that may impact the patient and are potential targets for quality assurance. Methods: As part of a wider study, a multi-disciplinary group of professionals aimed to define a list of morbidities linked to paediatric cardiac surgery that was prioritised by a panel reflecting the views of both professionals from a range of disciplines and settings as well as parents and patients. Results: We present a set of definitions of morbidity for use in routine audit after paediatric cardiac surgery. These morbidities are ranked in priority order as acute neurological event, unplanned re-operation, feeding problems, the need for renal support, major adverse cardiac events or never events, extracorporeal life support, necrotising enterocolitis, surgical site of blood stream infection, and prolonged pleural effusion or chylothorax. It is recognised that more than one such morbidity may arise in the same patient and these are referred to as multiple morbidities, except in the case of extracorporeal life support, which is a stand-alone constellation of morbidity. Conclusions: It is feasible to define a range of paediatric cardiac surgical morbidities for use in routine audit that reflects the priorities of both professionals and parents. The impact of these morbidities on the patient and family will be explored prospectively as part of a wider ongoing, multi-centre study.